FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI DALAM MENINGKATKAN PENDAPATAN PETANI PADI PERSPEKTIF EKONOMI ISLAM (Studi Kasus Di Desa Tangaran Kecamatan Tangaran) - Rojia; Ananda, Iva Ashari; Marina (Cross-Border Journal of Business Management, 2026)
This research is motivated by the existence of factors that influence production in increasing rice farmers' income from an Islamic economic perspective. Tangaran Village, Tangaran District, which has quite a lot of production factors so that it influences farmers' income a lot. The technology used in this research is. The theory of what factors influence paddy production and how production increases the income of paddy farmers. This research uses a descriptive qualitative approach, and includes a type of field research. The data collection techniques used are observation, interviews and documentation. The data used is primary income of the paddy farming community. The research data analysis technique is data reduction, submission of data, drawing conclusions. The technique for the validity of the data used is member checking. Based on the results of the research, it is concluded that the factors that influence production in increasing the income of rice farmers from an Islamic economic perspective are very much influenced by production factors and the income of rice farmers in Tangaran Village so that the income of farmers increases a lot, and many implement Islamic teachings. It has a positive impact on the economy of the local rice farming community, especially the community. Tangaran Village